The Influence of Competence and Motivation on Employee Performance at the Gereneng Village Office, East Sakra District - Supriadi Sansit; Yousf Bellin Swarli (Cigarskruie: Journal of Educational and Islamic Research, 2024)
This research aims to analyze the influence of competence and motivation on the performance of employees and staff at the Gereneng Village Office, East Sakra District. This research uses quantitative methods with a survey approach. Data was obtained through questionnaires distributed to employees and staff at the Gereneng Village Office. The data analysis technique used is multiple linear regression to find out how much influence competence and motivation have on employee performance. The research results show that competence and motivation have a significant influence on employee performance. High competency in employees is directly proportional to their increased performance. Apart from that, good motivation has also been proven to improve employee performance. The combination of adequate competence and high motivation produces optimal employee performance. These findings indicate that to improve the performance of employees and staff at the Gereneng Village Office, efforts are needed to increase competency through training and development as well as effective motivation management. In this way, it is hoped that employees and staff can work more productively and provide better services to the community.